Aspergillus niger beta-Glucosidase Has a Cellulase-like Tadpole Molecular Shape INSIGHTS INTO GLYCOSIDE HYDROLASE FAMILY 3 (GH3) beta-GLUCOSIDASE STRUCTURE AND FUNCTION - Lima, Marisa A.; Oliveira-Neto, Mario [UNESP]; Kadowaki, Marco Antonio S.; Rosseto, Flavio R.; Prates, Erica T. [UNESP]; Squina, Fabio M.; Leme, Adriana F. P.; Skaf, Munir S.; Polikarpov, Igor (Amer Soc Biochemistry Molecular Biology Inc, 2013)
Background: -Glucosidase completes cellulose enzymatic hydrolysis by releasing glucose from cellobiose. Results: SAXS experiments revealed that Aspergillus niger -glucosidase has a cellulase-like tadpole molecular shape, uncommon to enzymes that act on the soluble substrates. Conclusion: We show that AnBgl1 N- and C-terminal domains are linked by a long extended linker. Significance: Understanding AnBgl1 architecture is useful for comprehension of the enzyme-cell wall interaction and the process of biomass saccharification. Aspergillus niger is known to secrete large amounts of -glucosidases, which have a variety of biotechnological and industrial applications. Here, we purified an A. niger -glucosidase (AnBgl1) and conducted its biochemical and biophysical analyses. Purified enzyme with an apparent molecular mass of 116 kDa forms monomers in solution as judged by native gel electrophoresis and has a pI value of 4.55, as found for most of the fungi of -glucosidases. Surprisingly, the small angle x-ray experiments reveal that AnBgl1 has a tadpole-like structure, with the N-terminal catalytic domain and C-terminal fibronectin III-like domain (FnIII) connected by the long linker peptide (approximate to 100 amino acid residues) in an extended conformation. This molecular organization resembles the one adopted by other cellulases (such as cellobiohydrolases, for example) that frequently contain a catalytic domain linked to the cellulose-binding module that mediates their binding to insoluble and polymeric cellulose. The reasons why AnBgl1, which acts on the small soluble substrates, has a tadpole molecular shape are not entirely clear. However, our enzyme pulldown assays with different polymeric substrates suggest that AnBgl1 has little or no capacity to bind to and to adsorb cellulose, xylan, and starch, but it has high affinity to lignin. Molecular dynamics simulations suggested that clusters of residues located in the C-terminal FnIII domain interact strongly with lignin fragments. The simulations showed that numerous arginine residues scattered throughout the FnIII surface play an important role in the interaction with lignin by means of cation- stacking with the lignin aromatic rings. These results indicate that the C-terminal FnIII domain could be operational for immobilization of the enzyme on the cell wall and for the prevention of unproductive binding of cellulase to the biomass lignin.
Keywords: Enzyme Mechanisms; Enzyme Structure; Enzymes; Fungi; Glycobiology; Aspergillus niger; SAXS; -Glucosidase; Glycoside Hydrolase Family 3; Multidomain Proteins